IDENTIFICATION OF SOIL INSECT DIVERSITY AT SIRAH KENCONG TEA PLANTATION AS AN ATLAS SUPPORTING ANIMALIA : IDENTIFIKASI KEANEKARAGAMAN SERANGGA TANAH DI PERKEBUNAN TEH SIRAH KENCONG SEBAGAI ATLAS PENUNJANG MATERI ANIMALIA - Ayu, Ayu Siti Mariati; Sari Sofiana, Marinda; Nurul Malayahati, Eva (JOSAR (Journal of Students Academic Research), 2024)
This research purpose to determine the index of soil insect diversity, feasibility and student and teacher responses to the soil insect diversity atlas. Research and Development with the Borg and Gall used in the research method which is limited to the seventh stage. The instrument used was a questionnaire for expert validation, readability and response using a Likert scale. Analyzing the Diversity Index using the Shanon-Weiner formula. With descriptive qualitative as technigue data analysis . The results of the overall diversity index amounted to 2.29 while the diversity index (H') of stations 1, 2 and 3 were 2.32, 2.43 and 1.99 respectively. The results of the validation of material, language, and media experts respectively obtained a score of 84%, 93%, and 90% while the readability of teachers and students obtained a score of 95% and 96%. Teacher and student responses obtained a score of 98%, and 91%. So it can be concluded that the media Atlas of soil insect diversity can be used as a supporting media for animalia material.